Double Diamond Approach for Mobile-based UX: Connecting Students to Professional IT Projects - Farhantama, Andrean Miksa; Mardhia, Murein Miksa (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
Students at UAD can join various projects offered by their lecturers, including research, internships, assignments, and competitions. These opportunities are typically communicated through research workshops or WhatsApp groups. Currently, more lecturers are getting research projects that require students as technical members, but they need to be sure about the students' sufficient abilities. On the other hand, not all students receive this information, and project monitoring is often done informally via WhatsApp. All students should get projects so they can graduate from project management courses or internships. To address this, lecturers can help speed up the process of students getting projects by inviting students to join their projects. An application was proposed to streamline information dissemination, student selection, and project monitoring. The study employed the double diamond method—Discover, Define, Develop, and Deliver —to design the app's UI/UX prototype. Usability and user experience testing showed high success rates for both lecturer and student applications, with 91.81% and 84.54% respectively. The student app scored well on attraction (1.63), clarity (1.45), efficiency (1.70), accuracy (1.70), stimulation (1.95), and novelty (1.40). The lecturer app scored even higher on attraction (2.47), clarity (1.45), efficiency (2.25), accuracy (1.95), stimulation (2.65), and novelty (2.45).